Specific egg yolk immunoglobulin as a promising non-antibiotic biotherapeutic product against Acinetobacter baumannii pneumonia infection - Abolfazl Jahangiri (Nature Portfolio, 2021)
Abstract Acinetobacter baumannii is a serious health threat with a high mortality rate. We have already reported prophylactic effects of IgYs raised against OmpA and Omp34 as well as against inactivated whole-cell (IWC) of A. baumannii in a murine pneumonia model. However, the infection was exacerbated in the mice group that received IgYs raised against the combination of OmpA and Omp34. The current study was conducted to propose reasons for the observed antibody-dependent enhancement (ADE) in addition to the therapeutic effect of specific IgYs in the murine pneumonia model. This phenomenon was hypothetically attributed to topologically inaccessible similar epitopes of OmpA and Omp34 sharing similarity with peptides of mice proteins. In silico analyses revealed that some inaccessible peptides of OmpA shared similarity with peptides of Omp34 and Mus musculus. Specific anti-OmpA and anti-Omp34 IgYs cross-reacted with Omp34 and OmpA respectively. Specific IgYs showed different protectivity against A. baumannii AbI101 in the murine pneumonia model. IgYs triggered against OmpA or IWC of A. baumannii were the most protective antibodies. IgY triggered against Omp34 is ranked next after those against OmpA. The lowest protection was observed in mice received IgYs raised against the combination of rOmpA and rOmp34. In conclusion, specific IgYs against OmpA, Omp34, and IWC of A. baumannii could serve as novel biotherapeutics against A. baumannii pneumonia.